Influence of physicochemical properties of seed on template-free ferrierite synthesis and its application in oleic acid isomerization - Patil, Shrinidhi D.; Mohanty, Ananya; Kudalkar, Mahadev; Niphadkar, Prashant S.; Bhatte, Kushal D.; Bokade, Vijay V. (Journal of Chemical Sciences, 2025)
We have reported an effective, seed-assisted organic structure directing agent (OSDA) free synthesis of ferrierite (FER) zeolites. In the current study, we have observed effects of physicochemical properties of two different seeds over synthesis of FER zeolites. The physicochemical properties of seeds, such as particle size and phase purity impart significantly over crystallization time and overall synthesis duration, costs of process and crystalline nature of FER zeolites. It is noteworthy that particle size of seed mainly affects the kinetics of crystallization for concerned FER zeolites. The synthesized zeolites were well characterized by XRD, FESEM, TEM, Raman spectroscopy, 27Al and 29Si MAS NMR, EDAX and BET surface area analyser to get more insights. We also evaluated, the catalytic activity of synthesized FER zeolites in oleic acid isomerization study to derive branched-chain fatty acids formation and attempted their structure and catalytic activity relationship with respect to purity of phases in seed.
Keywords: crystallization kinetics; Ferrierite seed; oleic acid isomerization; OSDA-free synthesis